2010
DOI: 10.1111/j.1540-627x.2010.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Family-Owned Business Succession: The Influence of Pre-performance in the Nomination of Family and Nonfamily Members: Evidence from Spanish Firms

Abstract: Although family-owned business succession has been widely researched, very few studies investigate the relationship between preperformance and succession. Drawing on the agency and the resource-based view theories, we investigate how previous firm performance may influence the nomination of a family or a nonfamily member to top senior positions. We argue that positive firm performance will lead to the nomination of a family member, while negative firm performance leads to nonfamily nominations. Using a stepwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 81 publications
4
58
0
3
Order By: Relevance
“…The reason lies in the fact that according to the agency theory, managers are self-interested individuals (Davis, Schoorman, & Donaldson, 1997), driven by personal ego (Ramachandran & Jha, 2007) who act mainly in their own best interests, forsaking the interests of other shareholders and carry out activities that go against the maximization of shareholder's wealth. Hence, to reduce the agency problem, managers also have to be owners, so that maximum efforts can be expended for the improvement of firm value (Seifert et al, 2005) or for family to be involved in both ownership and management (Bocatto, Gispert, & Rialp, 2010).…”
Section: The Moderating Effect Of Family Ceomentioning
confidence: 99%
“…The reason lies in the fact that according to the agency theory, managers are self-interested individuals (Davis, Schoorman, & Donaldson, 1997), driven by personal ego (Ramachandran & Jha, 2007) who act mainly in their own best interests, forsaking the interests of other shareholders and carry out activities that go against the maximization of shareholder's wealth. Hence, to reduce the agency problem, managers also have to be owners, so that maximum efforts can be expended for the improvement of firm value (Seifert et al, 2005) or for family to be involved in both ownership and management (Bocatto, Gispert, & Rialp, 2010).…”
Section: The Moderating Effect Of Family Ceomentioning
confidence: 99%
“…A robust succession plan identifies a number of these traits and skills and ranks them from essential to desirable to nice to have. In turn, the management board informs plan members about the traits and skills it is seeking so that the process is transparent and well-understood by all members (Mehrabani, Mohamad, 2011;Bocatto et al, 2010). Internally communicating these traits also allows candidates to identify themselves as potential workers (Brent, 2013;Renz, 2010).…”
Section: X=f(y)mentioning
confidence: 99%
“…Many organisations discuss succession planning only when they need to replace some personnel. But to best prepare for the future and best serve their members, management should consider acting much earlier to establish succession policies and procedures that are crucial to board governance (Galagan, 2010;Bocatto et al, 2010). Succession planning is important because it ensures that management of organisations have high-functioning, dedicated and committed trustees who work toward great outcomes for the plan (Brent, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As some of these firms did not get procure the necessary skills to grow and keep the business sustainable. It was shown that companies' owners are strong believers in their stewardship responsibility in the interest of continuity from generation to generation (Bocatto, Gispert, Rialp, 2010). Abor and Biekpe (2007) conducted research in Ghana which focused on the corporate governance, ownership structure and performance of SMMEs and the financial gains that these SMMEs can make if they followed good corporate governance measures.…”
Section: Literature Review On Succession Planningmentioning
confidence: 99%
“…This then will maximize the company's value (Bartholomeusz and Tanewski, 2006). Bocatto, Gispert & Rialp (2010), investigated 86 nonfinancial firms listed on the Spanish Stock Exchange, to observe how their pre-performance influenced the nomination of a family or a non-family member to top senior positions. The research showed that failure to provide succession was a primary cause for the demise of family owned businesses.…”
Section: Literature Review On Succession Planningmentioning
confidence: 99%